The role of the local community in Pari city village in the development of Sri Mersing beach tourism in Serdang Bedagai district - Slamet Widodo; Ahmad Aswan Waruwu; Agung Putranto (SEAN Institute, 2024)
The purpose of this study is to analyze the participation of the community in Kota Pari village in the development of Sri Mersing Beach tourism before and after it was managed by the government. Support and participation of the local community are crucial in tourism development. The government is expected to play a role in encouraging increased community participation. However, in practice, government involvement in management can potentially have both positive and negative impacts on community participation. Through a qualitative descriptive method, this study examines the level of community participation in the development of Sri Mersing Beach tourism, currently managed by the government, using Arnstein's ladder of participation. The results show that the participation of the community in Kota Pari village in the development of Sri Mersing Beach tourism is at the level of tokenism or symbolic participation after Sri Mersing Beach was managed by the government. Therefore, the government's role, which is largely focused on physical development, needs to be accompanied by efforts to increase community participation to ensure its sustainability and continual improvement, thus achieving sustainable tourism.